Classroom Interaction in the EFL Speaking Class in Junior High School - Kurniawan, Made Budi (Universitas Pendidikan Ganesha, 2022)
The teaching and learning process is very dependent on the interactions that occur between teachers and students. The interaction occurs when the two subjects (teacher and student) speak. The purpose of this study is to analyze the types of interactions that were carried out during speaking class, teacher talk, and student talk. This study uses a qualitative design with research subjects were English teachers and 35 students in grade 8 at SMP Negeri 5 Singaraja. The data were obtained using observation and using the Foreign Language Interaction (FLINT) system as data analysis. There were three current flows of analysis method namely: data reduction, data display, and conclusion/verification. The result of the study reveals that there were seven types of classroom interaction. Those types of classroom interactions have the role to support the success of the learning process. The highest percentage of teacher talk is in teacher-whole class which the class is almost done with the all interaction by the teacher with the students.